SEJARAH PERUMUSAN PANCASILA PANCASILA SEBAGAI SISTEM FILSAFAT - Nela Kurniana; Kukuh Tri Karnandi; Muhammad Yusuf Bustomi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to find out about the history of the formulation of Pancasila and Pancasila, as a system of philosophy. The formulation of Pancasila began with the establishment of the Indonesian Independence Preparatory Investigation Agency (BPUPKI). The first meeting of the BPUPKI was held on May 29 to June 1 1945 as an independent Indonesian state. Pancasila as the basis of the state philosophy and philosophy of life for the Indonesian nation is a systematic and comprehensive value.